Waning neutralizing antibodies through 180 days after homologous and heterologous boosters of inactivated COVID-19 vaccine - Chen, Zhifei; Xie, Fangqin; Zhang, Hairong; Li, Dong; Zhang, Suhan; Zhang, Mengping; Li, Junrong; Xie, Jianfeng; Zhang, Lina; Yang, Xiuhui; Zhang, Dongjuan (Frontiers in Public Health, 2025)
To enhance the personal immunity to COVID-19, a third booster dose of inactivated COVID-19 vaccines program campaign was implemented in China. Our study endeavored to compare the dynamics of neutralizing antibodies generated by four distinct booster vaccines against three kinds of live SARS-CoV-2 virus (wild-type, Delta AY.23, and Omicron BA5.2). This cohort study involved 320 healthy individuals, who were randomly assigned to four groups, to receive boosters with inactivated vaccine (COVac and BIBP), the adenovirus type-5-vectored vaccine (Convidecia), and the recombinant protein-based vaccine (Zifivax), respectively, all the vaccines studied had the Wuhan variant as their parental variant. Participants were recruited from December 2021 to June 2022, with a follow-up period of 180 days. We evaluated humoral immune responses and their longevity by measuring the geometric mean titers (GMTs) of neutralizing antibodies against the SARS-CoV-2 virus at various time points post-boost. After 180 days of follow-up, 310 participants completed the study. Across all booster groups, neutralizing antibodies against the wild-type virus declined sharply within the first 90 days, accounting for an 81.24 to 92.34% reduction, then slowed down with gradually decreasing decay rates. By day 14 of post-boost, the ability to neutralize the Delta variant slightly diminished compared to the wild-type, whereas neutralizing antibodies against the Omicron variant exhibited a more pronounced decline, ranging from 10.78 to 19.88 times lower than those against the wild-type. Notably, heterologous boosting with the Convidecia vaccine maintained higher GMTs of neutralizing antibodies against both Delta and Omicron variants compared to the other boosters. At 180 days of post-boost, GMTs of neutralizing antibodies against SARS-CoV-2 had substantially decreased, yet individuals who received the Convidecia vaccine still exhibited higher titers than those who received other boosters. In summary, neutralizing antibody levels significantly waned 180 days after the third vaccine dose, with the most pronounced decline occurring within the initial 90 days. Heterologous boosting with Convidecia demonstrated a more robust, durable, and broad humoral immune response compared to boosting with inactivated vaccines or Zifivax, suggesting that adenovirus vector vaccines possess a special advantage in the realm of vaccine development for preventing infectious diseases.